2022
DOI: 10.1097/md.0000000000029100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the outcomes of hemorrhoidectomy and PPH in the treatment of grades III and IV hemorrhoids

Abstract: To investigate the clinical effect and outcome of traditional hemorrhoidectomy and procedures for prolapse and hemorrhoid (PPH) for the treatment of grades III and IV hemorrhoids.We retrospectively reviewed 1003 grades III and IV hemorrhoid patients who presented to our hospital. A total of 585 patients underwent PPH, and 418 patients underwent hemorrhoidectomy. The outcomes were 1-year recurrence, postoperative complications, surgery-related complications, and indicators.No significant difference between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The amount of thread hanging is mainly based on the comprehensive measurement of the degree of stenosis and hardness of the scar tissue. 10 Compared with direct incision of the stenosis ring, there was less bleeding after the stenosis ring was set in the treatment of rectal stenosis after PPH. 11 At the same time, slow cutting can prevent re-adhesive stenosis of the severed end of the stenosis ring.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of thread hanging is mainly based on the comprehensive measurement of the degree of stenosis and hardness of the scar tissue. 10 Compared with direct incision of the stenosis ring, there was less bleeding after the stenosis ring was set in the treatment of rectal stenosis after PPH. 11 At the same time, slow cutting can prevent re-adhesive stenosis of the severed end of the stenosis ring.…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al (2023) found that Xileisan temperature-sensitive gels could reduce inflammation and bleeding in the hemorrhoid mucosa in rats, possibly related to the inhibition of eNOS expression in the rat's hemorrhoid tissues. Zhang (2015a) found that Sihuang Hemorrhoids Ointment could improve local symptoms in a rat model of hemorrhoids, possibly related to the inhibition of iNOS expression. Zhang (2017b) found that the modified Huanglian Jiedu Decoction could reduce local inflammation in a rat model of hemorrhoids, improve edema and ulcer symptoms in the perianal area, and its mechanism of action might be related to the inhibition of iNOS expression.…”
Section: Inhibiting Nos Levels To Alleviate Varicose Veinsmentioning
confidence: 94%
“…Zhao (2013) found that Sanhuang Zhixue Capsule could significantly inhibit the expression of VEGF in the rat's rectal canal. Zhang (2015a) found that Si Huang Hemorrhoid Ointment could significantly inhibit the expression of VEGF in animal models of hemorrhoids using immunohistochemistry. Jia et al (2023) found that Xileisan temperature-sensitive gels could alleviate inflammation and reduce internal hemorrhoid bleeding possibly by inhibiting the expression of VEGF-A in rat hemorrhoid tissues.…”
Section: Inhibiting Angiogenesis To Delay the Development Of Hemorrhoidsmentioning
confidence: 99%
“…The most frequent post-operative issue is pain, but anal stricture and incontinence, albeit rare, may result from excessive tissue removal and damage to the sphincter muscles [66,68]. These can be avoided by retaining normal anoderm between excisions, not excising all hemorrhoid sacs at once for patients with extensive lesions, and performing careful dissection in the submucosal plane [69].…”
Section: Hemorrhoids Surgerymentioning
confidence: 99%